Language, writing, and mobility a sociological perspective - Coulmas, Florian (Oxford, [England] Oxford University Press, 2022)
This book brings together three subjects which command our attention because of their changing roles in everyday life, language, writing, and mobility. In different ways, borders are being crossed, redrawn, and redefined as we watch, and while comparable processes could be observed in the past, they are today more conspicuous than ever, being propelled by demographics, technological innovation, and consumer capitalism. The said three subjects interact in various ways and have an impact on language contact which, as this book is designed to show, are best captured by a processual view along the lines laid out for social analysis by Norbert Elias. The processual view of language and society adopted here is congenial with the sociolinguistic paradigm developed over the past several decades, with one important difference, it assigns writing a central position. Sociolinguistics has always concentrated heavily on speech and largely ignored writing, although the social importance of writing cannot be denied. Giving written language its due in this book, then, has four reasons. (1) Writing is the most consequential technology ever invented. (2) Writing both suggests stability and defines borders. (3) Linguistics, while emphasizing that writing is external to language, is nevertheless indebted for its analytic categories to writing. (4) By turning virtually everyone into a writer/producer of texts, the digital revolution has fundamentally changed communication patters in ways that impact both social formations and language. Computer mediated communication (CMC) has transformed the social functions of writing and, through it, language."--Publisher.
Includes bibliographical references (pages 162-184) and indexes.
Keywords: Sociolinguistics in literature; Sociolinguistics; Emigration and immigration -- History -- Social aspects